Adipocytes express tissue factor and FVII and are procoagulant in a TF/FVIIa-dependent manner. (3rd July 2019) - Edén, Desirée; Panagiotou, Grigorios; Mokhtari, Dariush; Eriksson, Jan W.; Åberg, Mikael; Siegbahn, Agneta
Abstract: Background: Tissue factor (TF) combined with its ligand FVII initiates blood coagulation and intracellular signaling. Obese and type 2 diabetic subjects have increased TF expression in their adipose tissue and an increased risk for thrombotic complications. Here we address the role of TF/FVII on adipocyte functions. Materials and methods: Subcutaneous fat was obtained by means of needle aspiration from healthy volunteers, and adipocytes were isolated after collagenase digestion. 3T3-L1 fibroblasts kept in culture were differentiated into adipocytes by addition of IBMX, dexamethasone, rosiglitazone, and insulin to the media. Proteins and mRNA were analyzed by western blot and RT-PCR. Coagulation activity was determined by a colorimetric FX-assay. Lipolysis was measured as free glycerol using a colorimetric method. Glucose uptake was evaluated by scintillation counting of D-[U- 14 C] glucose. Results: In isolated human primary adipocytes we found expression of TF and FVII. TF expression was confirmed in 3T3-L1 adipocytes, and both cell types were found to be procoagulant in a TF/FVIIa-dependent manner. FXa was generated without FVIIa added to the coagulation assay, and active site-inhibited FVIIa blocked FXa formation, supporting our finding of FVII production by human primary adipocytes. There was no evidence for a role of TF in either lipolysis or glucose uptake in our experimental settings. Conclusion: Human primary adipocytes express active TF and FVII, and the TF/FVIIa complex formed on the adipocyte surface can activate substrate FX. Whether the TF/FVIIa complex conveys signaling pathways leading to biological functions and has any biological activity in adipocytes beyond coagulation remains to be elucidated.